2007
DOI: 10.1007/s10653-006-9074-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic occurrence in Brazil and human exposure

Abstract: Environmental exposure to arsenic (As) in terms of public health is receiving increasing attention worldwide following cases of mass contamination in different parts of the world. However, there is a scarcity of data available on As geochemistry in Brazilian territory, despite the known occurrence of As in some of the more severely polluted areas of Brazil. The purpose of this paper is to discuss existing data on As distribution in Brazil based on recent investigations in three contaminated areas as well as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 18 publications
1
14
0
9
Order By: Relevance
“…Estas amostras foram coletadas no interior das minas do Chico Rei (CR) e Passagem (PM), situadas em Ouro Preto, e Passagem de Mariana, respectivamente, no Quadrilátero Ferrífero -MG, onde há a contaminação natural e antropogênica por As de águas, solos e sedimentos de rios, relacionada com a mineração secular de ouro. 14,15 Em cada local de amostragem foram coletadas seis alíquotas de água, de 200 mL, que foram filtradas através de uma membrana de acetato de celulose de 0,45 µm (Millipore) e colocadas em tubos de centrifuga esterilizados. Em uma das alíquotas foram medidos diretamente, in situ, o pH, Eh, a condutividade e a temperatura das tabela 1.…”
Section: Amostras De áGua Subterrâneaunclassified
“…Estas amostras foram coletadas no interior das minas do Chico Rei (CR) e Passagem (PM), situadas em Ouro Preto, e Passagem de Mariana, respectivamente, no Quadrilátero Ferrífero -MG, onde há a contaminação natural e antropogênica por As de águas, solos e sedimentos de rios, relacionada com a mineração secular de ouro. 14,15 Em cada local de amostragem foram coletadas seis alíquotas de água, de 200 mL, que foram filtradas através de uma membrana de acetato de celulose de 0,45 µm (Millipore) e colocadas em tubos de centrifuga esterilizados. Em uma das alíquotas foram medidos diretamente, in situ, o pH, Eh, a condutividade e a temperatura das tabela 1.…”
Section: Amostras De áGua Subterrâneaunclassified
“…Furthermore, pesticides, herbicides, wood preservatives, burning of fossil fuels, fertilizers, smelting of gold, lead, copper and nickel, and production of iron and steel are the main anthropogenic sources of As (Mandal;Suzuki, 2002). surface water bodies with values higher than10 µg L -1 have been verified by studies of human exposure in the Quadrilátero Ferrífero area, Minas Gerais state (Figueiredo, 2006) and in the municipality of Santana, Amapá state (Figueiredo et al, 2007). The main source of contamination at these sites is the mining of metals, mainly gold, iron and manganese.…”
Section: Arsenic In the Environmentmentioning
confidence: 74%
“…When comparing the As urine levels of these patients with the ones of healthy subjects, Ruiz-Navarro et al (1998) did not find any statistical difference, indicating that regulation of As in the human body is independent of these diseases. Figueiredo et al (2007) summarized previous studies in a series of Brazilian zones highly impacted by mining (Au, Pb-Zn, …), where water run-off was found with total As up to 2,980 lg/l and As(III) up to 86 lg/l; they discussed these data and complementary human monitoring (urine, hairs) on various populations, according to various factors including local climate. Concerning As concentration in urine, Ma and Le (1998) observed that the ingestion of arsenosugars-containing food (like i.e.…”
Section: Arsenic Exposure and Health Effectsmentioning
confidence: 97%